DYNAMIQUE SPATIALE DES RESSOURCES NATURELLES EXPLOITÉES DANS LA COMMUNE RURALE DE WATENI (CERCLE DE SIKASSO AU MALI) - Fane, Siaka (European Scientific Journal, ESJ, 2015)
Wateni is one of the 703 rural communes in Mali. Its geographical situation makes it part of southern Mali in Sikasso Region. In this location, it benefits by a simple relief and a climate limited by the isohyets 1000 mm in the south and 800 mm in the north. Under this climate called north Malian Sudanese the population perform various production activities. The exploitation of natural resources caused by the practice of different activities constitutes a factor engaging the area into dynamics. Thus, our work aims at the knowledge of the pace and the extent of the natural resources dynamics on the one hand, and on the other hand at the present agrarian landscape figured and its effects on the agricultural productions. For that an exploitation of landsat images has been done. These images were of 1984; 1999 and 2006. Their treatment, classification the files conversion into shape format on ENVI software, the files transformation on MapInfo have enabled to realize maps of occupancy mode at each of the dates; The extracted information revealed enough availability of resources. As far as the exploitation of the important resource potential is concerned. The agricultural production is thought of as a priority activity. Its space registration accounts for a slow dynamics of resources and the shaping of a fragmented and segmented agrarian landscape. This results in production that do not satisfy the consumer needs of the production units. To face up to production in deficit and the problems of developpement, a restructuring of eagrarian landscape can be initiated by the local conucillors through reallocation operation.